Education inequalities in Latin America and the Caribbean - Raquel Fernández; Carmen Pagés; Miguel Székely; Ivonne Acevedo (Inter-American Development Bank (IDB), 2023)
Education is a crucial asset for a country's economic prospects and for its inhabitants. In addition to its direct impact on growth via the accumulation of human capital, it is a critical ingredient in producing an informed citizenry, enhancing their ability to obtain and exert human and political rights and their facility to adapt to changing environments (generated by, e.g., technological or climatic change) among other benefits. In this chapter, we study education inequality in LAC (both in quantity and quality), assess how it emerges and amplifies or dampens existing inequalities, and examine the interaction of education inequality with other forms of inequality, primarily income and labor market outcomes. Our analysis is based on primary data from multiple sources.
Keywords: I24; I25; I26; 330; Education and Inequality; Education and Economic Development; Returns to Education